326 Student Perceptions of Neurosurgery: Evaluating the Role of Undergraduate Neuroscience Societies. (4th May 2021) - Aw, K L; Lee, S H; McLarnon, M; Raveendran, D; O'Callaghan, C; Mullan, G; Fearon, M; Samuel, S; Sekar, V; Rogan, P
Abstract: Introduction: Many institutions lack an organized system of informal network for medical students wishing to explore neurosurgery. We sought to evaluate the role of extracurricular neurosurgical events in influencing student perceptions of neurosurgery. Method: Participants for this study were recruited from a neurosurgical careers seminar and practical workshop. Responses were collected prospectively using a multi-method strategy consisting of closed and open-ended questions. Additionally, semi-structured interviews were conducted to gain a deeper insight of students' evaluation of these events and their perceptions of neurosurgery. Results: A total of 124 students attended our extracurricular neurosurgery events. These events showed benefits in clinical knowledge and career planning. Students perceived the practical workshops to be useful in improving their basic surgical skills. Semi-structured interviews revealed that students felt their opportunities in exploring clinical neurosciences to be limited, which was seen as contributing towards the wider culture of neurophobia. Conclusions: Undergraduate neuroscience societies provide useful educational platforms for students interested in neurosurgery, even in regions lacking institutional neuroscience networks. To help mitigate the wider culture of neurophobia, undergraduate neuroscience societies should focus on non-academic aspects of neurosurgery that are more personal and engaging, in an effort to spark interest in those who have had little exposure to the specialty.